Categorization and Analysis of Student Errors in the Serbian Language Exam Classes - Marina S. Janjić; Aleksandar M. Novaković (University of Belgrade, Teacher Education Faculty, 2020)
The subject of this paper is identifying the most common students' mistakes in teaching lessons of the Serbian Language which are a part of the exam for the academic course Professional Methodological Practice of Teaching Serbian Language at the Faculty of Philososphy in Niš. By analyzing the data obtained by observing the lessons taught by the students of the Serbian Language at the Faculty of Philososphy in Niš during the four-year period (2015/16 to 2018/19), the authors found and analyzed typical errors, classifying them into six categories: errors in methodological lesson management, ignoring teaching principles, a lack of the required class structure, an incorrect application of teaching methods, incorrect application of teaching and technical aids, and an unbalanced behaviour towards students. As there has been no paper dealing with a similar topic so far, this research should be instructive for students, in terms of offering them guidelines for organizing and taking these exams and state teaching license exams. The obtained results are indicative of the complexity of teaching theory (developmental and pedagogical psychology and didactics) that should be linked to academic disciplines (linguistics, theory of literature, and the art of literature) in the process of methodological design of the lessons of Serbian language and Literature.